(untitled) (Research, Society and Development, 2024)
Emergency contraception, also known as the "morning after" pill, is a method to reduce the risk of pregnancy after practicing unprotected sex. The feasibility and low cost of the medication skyrocketed the sales of the "morning after" pill and increased its misuse. The present study aimed to describe the use of the morning-after pill intake among health students at the University Center of Maceió-Alagoas (Brazil). A descriptive and quantitative study was conducted using electronic formularies hosted on the Google Forms platform. The study population was female students enrolled in health graduate programs at the Cesmac University Center. Data extracted from the formularies showed that most subjects (70.7%) disclosed taking a" morning after" pill at least once. Twenty-two percent of the students claimed taking the emergency contraception only once, while 28% reported taking the pill two to three times, and 20,5% four or more times. Furthermore, 45.3% of the interviewees admitted to relying on the "morning after" pill and neglecting other contraception methods. Nonetheless, 84.5% of the students declared to be fully aware of the consequences involving abusive use of the "morning after" pill. Our research reveals a concerning increase in the indiscriminate use of emergency contraception. This trend is linked to adverse effects on women’s health, including breast cancer, uterine cancer, and infertility. Also, the pill is ineffective in preventing sexually transmitted infections.